Education as right: the construction of deaf people place in Brazilian education (Research, Society and Development, 2022)
The insertion of the deaf people in the Brazilian educational system took place through a slow, gradual process, full of setbacks, in such a way that even though it has always existed, the recognition of the deaf and their rights, as well as people with disabilities in general, is essential, a recent achievement. In this way, this essay aims to trace the process of construction of the space for the deaf in Brazilian education, based on an international and national historical overview, placing the contribution of important names responsible for the creation of institutions and the law of the deaf community in the country. Therefore, the methodology adopted was a bibliographic review, in addition to the analysis containing a nature of the investigation, it presents itself as exploratory research. With that, we were able to conclude that despite the historical setbacks and progress in the achievements of the law until of the current legislation and existing institutions, they guarantee law to education for the deaf community. However, the challenges don't stop there, since the complexity of social relationships is also embedded in the multiple varieties of disabilities that sometimes relate to the deaf people.